An in-situ approach for preparing atom probe tomography specimens by xenon plasma-focused ion beam - Halpin, J; Webster, R; Gardner, H; Moody, M; Bagot, P; MacLaren, D (Elsevier, 2019)
A method for the rapid preparation of atom probe tomography (APT) needles using a xenon plasma-focussed ion beam (FIB) instrument is presented and demonstrated on a test sample of Ti-6Al-4V alloy. The method requires significantly less operator input than the standard lift-out protocol, is site-specific and produces needles with minimal ion-beam damage; electron microscopy indicated the needle's surface amorphised/oxidised region to be less than 2 nm thick. The resulting needles were routinely analysable by APT, confirming the expected microstructure and showing negligible Xe contamination.